Outcome of Subarachnoid Block with Low Dose Bupivacaine and Fentanyl for Lower Limb Vascular Surgeries in Patients with Coronary Artery Disease - Abbasi, Md Mahmud; Shaheen, Md Shafiul Alam; Ahmed, Raju; Saklayen, SMG; Alam, Md Mahbubul (Community Based Medical Journal, 2024)
Subarachnoid block (SAB) with local anesthetics and opioids (fentanyl) and able to perform spinal anesthesia because of the synergistic effects and allow top use of low dose local anesthetics which results in a stable hemodynamic state. A randomized clinical trial was conducted to observe the cardiovascular effects of subarachnoid block (SAB) with low dose bupivacaine and fentanyl on patient with coronary artery disease, between January 2021 and December 2022. A total of 36 patients who had known case of coronary artery disease. All patients underwent spinal block for lower limb surgery with 7.5 mg hyperbaric bupivacaine 0.5% and 25 µg fentanyl. In each patient, 1 mg I/V midazolam was used and if needed subsequent may be given. Complications related to anesthesia such as hypotension, bradycardia, vasopressor need, and blood or volume use were recorded. Our study shows at the 90-minutes of spinal block, patients with EF ≤40% experienced a decrease of 10.5% in systolic blood pressure, while those with EF>40% experienced a larger decrease of 19%. At the 90-minutes of spinal block, percentage decrease was higher in the EF>40% group (19.5% vs. 14%) in diastolic blood pressure. At the 90-minutes of spinal block, patients with EF ≤ 40% experienced a decrease of 13% in MAP, while those with EF>40% experienced a larger decrease of 19%. The findings demonstrate that patients with EF>40% exhibited larger percentage decreases in systolic blood pressure, diastolic blood pressure, and MAP compared to those with EF ≤40%. The difference was statically significant (P<0.05). Our study recommends subarachnoid block with low dose of bupivacaine and fentanyl is effective in lower limbs surgeries for patients with coronary artery disease particularly with low EF. CBMJ 2024 July: vol. 13 no. 02 P: 169-175